Evaluasi Kinerja Saluran Pemasaran Komoditas Buah Naga (Hylocereus polyrhizus) di Kabupaten Bulukumba Menggunakan Importance Performance Analysis (IPA) - Halim, Hasriliandi; Zailan, Ahmad (CV. SINAR HOWUHOWU, 2026)
Dragon fruit is a leading horticultural product that is growing rapidly in Bulukumba Regency. However, the effectiveness and performance of marketing channels remain a major issue affecting the level of satisfaction of business actors, especially farmers. This study aims to evaluate the performance of dragon fruit marketing channels in Bulukumba Regency using the Importance Performance Analysis (IPA) method. This study was conducted through a survey of farmers, marketers, and loyal consumers using a five-point Likert scale questionnaire to measure the level of importance and performance of marketing attributes. The analysis results show that there are several marketing attributes that are in Quadrant I (top priority), namely selling price, price stability, and payment speed. Attributes in this quadrant require immediate improvement, while in Quadrant II (maintain) there are no attributes in this quadrant. Then in Quadrant III (low priority) only the attribute of market information transparency is in this quadrant. In Quadrant 4 (excessive) there are attributes such as marketing costs, ease of market access, and the relationship between farmer traders and loyal consumers.